2020
DOI: 10.1002/pat.5076
|View full text |Cite
|
Sign up to set email alerts
|

An ultrafast and clean method to manufacture poly(vinyl alcohol) bead foam products

Abstract: Poly (vinyl alcohol) (PVA) foam is a promising environment‐friendly packaging material due to the good biodegradability and excellent mechanical properties. Besides, PVA can be produced on a large scale viathe non‐petroleum routes. However, the preparation of complex‐shaped PVA foam products has not been realized, because PVA is a water‐soluble and semi‐crystalline polymer with a high melting temperature (226°C), which cannot be welded through the conventional bead foaming technology. In this article, a clean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The soft segment in the polymer plays a significant role in absorbing CO 2 gas. , When the polymer has a higher crystalline hard segment, the chances of CO 2 being absorbed are lower because of the barrier effect of the crystalline region. , For reference, melting and crystalline peaks of different grade TPU samples used in this study are analyzed, and the results are shown in Figure S1. DSC curves help differentiate the different grades of the polymer through their melting behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The soft segment in the polymer plays a significant role in absorbing CO 2 gas. , When the polymer has a higher crystalline hard segment, the chances of CO 2 being absorbed are lower because of the barrier effect of the crystalline region. , For reference, melting and crystalline peaks of different grade TPU samples used in this study are analyzed, and the results are shown in Figure S1. DSC curves help differentiate the different grades of the polymer through their melting behavior.…”
Section: Resultsmentioning
confidence: 99%
“…55,60 The final part properties are similar to EPP. 55,60 In a recently published scientific study, Xu et al 61 presented another interesting representative of a biodegradable bead foam. They realized the development of PVA bead foam products based on microwave foaming and sintering.…”
Section: Biopolymer-based Bead Foamsmentioning
confidence: 99%
“…Recently, the working group of Altstadt realized the welding of chain extender-modified poly(butylene terephthalate) (PBT) beads using high-pressure steam (13−17 bar) for the first time. 14 Microwave irradiation was also applied to weld the polymer beads, 15 although it is hard to control and the related welding mechanism is not yet clear. Therefore, there is an urgent need to develop an advanced and low-cost strategy for fabricating these highstrength, heat-resistant, and lightweight polymer bead foams.…”
Section: Introductionmentioning
confidence: 99%